Protocol for the assessment of the development of pragmatic competencies in early childhood (PDP-PI) - Junquera, Cristina; Zubiauz, Begoña (Frontiers in Psychology, 2024)
The design of a Protocol for the Assessment of the Development of Pragmatic Competences in Early Childhood (PDP-PI) and the preliminary data obtained in a comparative study in three, four and five-year-old school children are presented. The design of the protocol is based on a model of global understanding of pragmatics that considers essential to include linguistic, intersubjective and social aspects in order to make an adequate assessment of development. Based on the taxonomies of communicative functions (Halliday, 1975;McShane, 1980), four basic competencies are described (Interactional, Referential, Subjective and Figurative). These competencies make it possible to categorize most of the linguistic emissions in early childhood.The PDP-PI presents two novelties with respect to other assessment systems: (a) it allows detecting the degree of a skill development (not only the presence/absence), (b) it includes items to assess the comprehension of pragmatics. The PDP-PI was used with 40 students of kindergarten education, divided into three groups according to school year. The results -Duncan's post hoc test -confirm the existence of significant differences between the different age groups in all competencies, except for referential competence. Construct validity was assessed by means of an inter-rater test (Fleiss' Kappa = 0.76; Krippendorff's Alpha = 0.76), and content validity was assessed by analyzing the correlations between the four competencies of the protocol. Significant correlations were found between all the competencies, except the relationship between the Referential and Interactional competencies. The data obtained in this study are preliminary, but they show that there is an evolution in the management of pragmatic skills, throughout early childhood, towards more complex and context-appropriate interactions. It is necessary to advance in procedures that discriminate against this evolution to establish developmental profiles which favor the detection of pragmatic difficulties or disorders at early ages.